The ‘afw Principle and The Indonesian Restorative Justice System - Alwy, Muhammad Rijaldy Alwy (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This paper explains the implementation of the ‘afw principle, a forgiveness principle known in Islamic criminal law, as an objective of Restorative Justice. Although the restorative justice has not been regulated in specific and comprehensive legislation in Indonesia, the restorative justice is currently regulated in at least three different institutional regulations, including the Circular Letter of the Chief of the Indonesian Police Number SE/8/VII/2018 (SE Kapolri), the Regulation of Indonesian Attorney Number 15 of 2020 (Perja), and the Decree of the Director General of the General Judiciary Body Number 1691/DJU/SK/PS.00/12/2020 (SK Dirjen Badilum). The three regulations provide a broad and slightly different explanation of how restorative justice objective is, which is likely to be interpreted in different means. However, the three institutional regulations have a similar approach to reconcile the victim and the perpetrator. The reconciliation seems to be a predominant restorative justice objective to enforce a criminal offence in Indonesia. This research uses a doctrinal methodology by analysing primary data sources, such as Indonesian legislation and Islamic sources of law, and secondary sources from relevant literature. The result indicates that there has not been comprehensive Indonesian legislation on restorative justice, particularly in terms of the objective. Incorporating the ‘afw principle as a restorative justice objective will provide more sense of justice for the victim and the alleged offender.